Shum et al 3D usat genotypes - Shum, Peter; Pampoulie, Christophe; Kristinsson, Kristján; Mariani, Stefano (Dryad Digital Repository, 2015)
Microsatellite data previously genotyped by Stefansson et al Heredity (2009) 102, 514–524.